Daily Stock Price Forecasting of PT Astra Agro Lestari (AALI) Using Arima and Arch-Garch Models - Azizah Rizki Amelia; Siti Nurhaliza; Zhakira Cantika Dewi; Agus Rifai (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The capital market serves as a vital investment channel where stock prices exhibit dynamic fluctuations influenced by macroeconomic factors and market sentiments. This study estimates daily stock prices of PT Astra Agro Lestari Tbk (AALI), a leading palm oil company, using hybrid ARIMA-ARCH-GARCH models. Employing quantitative time series analysis, the population comprises all daily AALI stock prices from January 1, 2021, to June 30, 2025 (1,145 observations), sampled purposively via Investing.com data. Analysis techniques include ADF stationarity tests, ACF-PACF correlograms, AIC/SC/HQ model selection, ARCH-LM heteroskedasticity tests, and forecasting accuracy evaluation. Results identify ARIMA(1,1,1) as optimal for mean modeling and GARCH(2,1) for volatility, achieving 53% average forecasting accuracy for July 31-August 5, 2025. The hybrid model effectively captures price patterns despite external influences.